Reformulating Organ Transplantation Policies Through Comparative Perspectives on Human Trafficking Laws in Indonesia and The Philippines - Iqbal, Muhamad; Indriani, Iin; Susanto; Nunna, Bhanu Prakash (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2025)
With the help of new technologies, the healthcare industry has made significant progress in addressing various diseases, including organ transplantation as a medical innovation to overcome organ failure. However, Indonesia continues to face an imbalance between organ demand and available donors, resulting in illicit practices and potential human organ trafficking. Using a normative juridical and comparative approach, this study analyses the legal frameworks in Indonesia and the Philippines regarding the prevention and punishment of organ trafficking. The findings show that Indonesia’s legal system lacks a coherent structure to regulate organ transplantation, leaving loopholes that allow exploitation under kinship-based donations, while the Philippines enforces a more detailed regulatory and institutional mechanism. Consequently, this study concludes that a reformulation of Indonesia’s criminal policy on organ transplantation is essential to integrate human trafficking perspectives, strengthen enforcement mechanisms, and align national regulations with international bioethical and legal standards.